National Consciousness: Meaning and Problem for Elder Schoolchildren - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 1999)
The article analyses the meaning and the problems of national consciousness. Initially it is based on the different views given about the notion of consciousness. Then the specific role of affective element in its structure is identified. At the same time we try to characterize the emotions of schoolchildren of higher classes and discover their connection to their nation.